Alterations of gray matter volume and functional connectivity in patients with cognitive impairment induced by occupational aluminum exposure: a case-control study - Huaxing Meng; Bo Liu; Xiaoting Lu; Yan Tan; Shanshan Wang; Baolong Pan; Hui Zhang; Qiao Niu (Frontiers in Neurology)
BackgroundCognitive impairment (CI) is a condition in which an individual experiences noticeable impairment in thinking abilities. Long-term exposure to aluminum (Al) can cause CI. This study aimed to determine the relationship between CI and MRI-related changes in postroom workers exposed to Al.MethodsThirty patients with CI and 25 healthy controls were recruited. Plasma aluminum levels were measured using inductively coupled plasma-mass spectrometry. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA) and an auditory-verbal learning test (AVLT). All participants underwent magnetic resonance imaging scans. 3D T1-weighted anatomical images and resting-state functional magnetic resonance imaging data were acquired, and voxel-based morphometry and ROI-based FC were used for analysis. A mediation analysis was also conducted.ResultsPlasma aluminum levels were significantly higher in the CI group than in the normal control group. The gray matter (GM) volume in the left caudate and bilateral hippocampus was lower in the CI group and was positively correlated with cognitive scale scores. There was no significant difference in functional connectivity (FC) between the left caudate and the whole brain between the two groups. Significant alterations in hippocampal FC were observed in certain brain areas, mainly in the left cerebellar vermis, left middle frontal gyrus (BA9), and right superior frontal gyrus relative to the supplementary motor area (BA6). The FC coefficients were also associated with cognitive scale scores. Furthermore, plasma Al concentration was negatively correlated with the Montreal Cognitive Assessment score, bilateral hippocampal GM volume, and FC coefficient between the left hippocampus and left cerebellar vermis. Mediation analysis showed GM alteration of left caudate and bilateral hippocampus and FC alteration of left hippocampus to left cerebellar vermis could explained 19.80–32.07% of the effect of MoCA scores change related to Al exposure, besides the GM alteration of right hippocampus acted as indirect mediator (68.75%) of the association between Al and AVLT delayed recall scores.ConclusionOur data indicates that alterations in the structure and function of special brain domain, especially the hippocampus, are associated with Al-induced CI. These brain regions can partly explain the effect of Al on cognitive impairment.